Thinking big: How to use theory of change for systems change - and Abercrombie, Rob; Boswell, Katie; Thomasoo, Rosanna (NPC, 2018)
We think that, applied well, theory of change can support charities and funders to take a systemic approach to their work. This report identifies five common pitfalls that organisations fall into when using theory of change, and walks through five rules of thumb that will help organisations to use the approach to tackle complex problems. We think that, applied well, theory of change can support charities and funders to take a systemic approach to their work. This report identifies five common pitfalls that organisations fall into when using theory of change, and walks through five rules of thumb that will help organisations to use the approach to tackle complex problems.